River Streamflow, Remotely Sensed Water Quality, and Benthic Composition of Previously Undescribed Nearshore Coral Reefs in Northern Puerto Rico - Torres-Pérez, Juan L.; Ramos-Scharrón, Carlos E.; Hernández, William J.; Armstrong, Roy A.; Barreto-Orta, Maritza; Ortiz-Zayas, Jorge; Guild, Liane S.; Viqueira, Roberto (Frontiers in Marine Science, 2021)
Land-based sediment stress represents a threat to many coral reefs in Puerto Rico primarily as a result of unrestricted land cover/land use changes and poor best management practices. The effects of such stresses have been documented along most coasts around the island. However, little attention has been paid to reefs located on the north coast, and very little is known about their composition and current state. Here, we present a study characterizing riverine inputs, water quality conditions, and benthic composition of two previously undescribed coral reefs (Tómbolo and Machuca reefs) located just eastward of the Río Grande de Manatí outlet in north-central Puerto Rico. This study utilizes a time series of remotely sensed ocean color products [diffuse vertical attenuation coefficient at 490 nm (Kd490) and chlorophyll-a concentration (Chl-a) estimated with data from the Visible Infrared Imaging Radiometer Suite (VIIRS)] to characterize water quality in this coastal region. In general, the months with relatively high mean daily river streamflow also coincide with months having the highest proportion of eastward wave direction, which can promote the eastward influence of river waters toward the two coral reefs sites. Kd490 and Chl-a showed a higher riverine influence closer to the watershed outlet. Kd490 and Chl-a monthly peaks also coincide with river streamflow highs, particularly at those pixels closer to shore. Tómbolo Reef, located farther eastward of the river outlet, shows a well-developed primary reef framework mainly composed of threatened reef-building species (Acropora palmata, Pseudodiploria) and high coral cover (19–51%). The benthos of Machuca Reef, located closer to the river outlet, is dominated by macroalgae with a significantly lower coral cover (0.2–2.7%) mainly composed of “weedy” coral species (Porites astreoides and Siderastrea radians). Cover of major benthic components correlates with distance from the river outlet, and with gradients in Kd490 and Chl-a, with higher coral cover and lower macroalgal cover farther from the river outlet. Coral cover at Tómbolo Reef is higher than what has been reported for similar sites around Puerto Rico and other Caribbean islands showing its ecological importance, and as up until now, an unrecognized potential refuge of reef-building threatened coral species.